2017
DOI: 10.3389/fimmu.2017.00024
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Impaired in Neutrophils from Streptozotocin-Induced Diabetic Rats

Abstract: We tested the hypothesis that changes reported on functions of neutrophils from streptozotocin-induced diabetic rats involve autophagy impairment. Wistar rats were rendered diabetic by streptozotocin injection (65 mg/kg, i.v.), and the measurements were carried out 2 weeks afterward. Neutrophils were collected through intraperitoneal cavity lavage after 4 h of i.p. oyster glycogen type 2 injection. Neutrophils cultured with PMA (20 nM) for 1 h were used for analysis of plasma membrane integrity, DNA fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…It has been reported that alterations in mitochondrial function cause a decrease in the membrane potential (Δψ m ), affecting the metabolic activity and causing a decrease in the amount of ATP, with the consequent low production capacity of ROS. The alteration of the mitochondrial processes results in an altered phagocytic capacity and chemotaxis of the neutrophils 52 , 53 . When bone marrow isolated neutrophils were exposed to LPS, there was a slight increase of the Δψ m loss.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that alterations in mitochondrial function cause a decrease in the membrane potential (Δψ m ), affecting the metabolic activity and causing a decrease in the amount of ATP, with the consequent low production capacity of ROS. The alteration of the mitochondrial processes results in an altered phagocytic capacity and chemotaxis of the neutrophils 52 , 53 . When bone marrow isolated neutrophils were exposed to LPS, there was a slight increase of the Δψ m loss.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, enhanced levels of circulating FFA and triacylglycerols cause insulin resistance and also neutrophilic inflammation (53, 54). Neutrophils from streptozotocin-induced diabetic rats exhibit defective autophagy, depolarized mitochondrial potential, and low ATP levels (116). Homocysteine, a sulfur-containing amino acid, levels increased significantly during diabetes and also induced NETosis (134).…”
Section: Metabolic Adaptations In Neutrophils During Pathological Conmentioning
confidence: 99%
“…In addition to chemotaxis, other neutrophil functions are also altered in diabetes, such as phagocytosis, bactericidal activity, and ROS production, which contribute to the high incidence and severity of infections in diabetic patients ( 48 ). Thus, we explored whether glucagon could impact ROS generation by neutrophils in vitro and observed that it inhibited zymosan A-induced ROS production by murine neutrophils in vitro .…”
Section: Discussionmentioning
confidence: 99%